OPTIMALISASI PERAN PANGKALAN TNI AL DALAM RANGKA PEMBENTUKAN KOMPONEN CADANGAN (Studi di Lantamal III Jakarta) - , SUDARSONO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research (1) aims at : review the role of an important naval base in order the formation of naval reserve component can walk more optimal, (2) should review what problems faced in the formation of naval reserve component, and (3) review efforts in optimal the role of an important naval base in order the formation of naval reserve component This research uses a qualitative method, in which more data analysis techniques in conjunction with the current data collection by researchers in the field and a miniature grand tour question, the analysis of the data analysis domain. The research is located in the region of the Navy Main Base III Jakarta, where data collection is done through observation, literature study and interviews conducted for commanders of the Navy Main Base III Jakarta, Operations Assistant of the Navy Main Base III Jakarta, Personnel Assistant of the Navy Main Base III Jakarta and Kadispotmar Lantamal. The results showed that: (1) the role of the Navy Base in the formation of reserve components have not been going well, since the establishment of a centralized reserve component still starts from the institutional role, a role in the recruitment and training in coaching roles. (2) there are still some obstacles encountered in carrying out its role that is not the level of authority, no part of a specially handle of naval reserve component in the organizational structure Dispotmar, and implementation of recruitment is still not handed over to the Navy Main Base III Jakarta in full. (3) need to look for a solution to resolve it through the optimization of the role of the efforts of (a) implementation of institutional aspects of the strategy through the addition of the position kasubdis in the Dispotmar organizational structure, arrange and organize training organization authority level of each actor in the formation of reserve components. (b) The application of recruitment strategies through: the arrangement of functions and principles of recruitment, organizing the implementation of the socialization phase of recruitment, data collection, sorting, calling, screening, selection and appointment / establishment. (c) implementation of development strategies by developing the concept of organizing training exercises starting from the planning, preparation, execution and reporting. Base role in the formation of reserve components need to be optimized so that it will materialize in a reserve component of the posture can be a major component of the multiplier.